2012
DOI: 10.1175/jcli-d-11-00547.1
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Heat Transport and Water Vapor Greenhouse in a Warm Equable Climate: A New Look at the Low Gradient Paradox

Abstract: The authors study the role of ocean heat transport (OHT) in the maintenance of a warm, equable, ice-free climate. An ensemble of idealized aquaplanet GCM calculations is used to assess the equilibrium sensitivity of global mean surface temperature (T) and its equator-to-pole gradient (DT) to variations in OHT, prescribed through a simple analytical formula representing export out of the tropics and poleward convergence. Lowlatitude OHT warms the mid-to high latitudes without cooling the tropics; T increases by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 80 publications
9
78
1
Order By: Relevance
“…In MPI-ESM, the atmosphere compensates for the decrease in the meridional ocean heat transport, implying an increased atmospheric heat transport (not shown), as also suggested by Rose and Ferreira (2012). A deeper analysis of the atmo- spheric compensation and changes in the atmospheric heat transport is needed but is beyond the scope of our study.…”
Section: Discussionsupporting
confidence: 55%
“…In MPI-ESM, the atmosphere compensates for the decrease in the meridional ocean heat transport, implying an increased atmospheric heat transport (not shown), as also suggested by Rose and Ferreira (2012). A deeper analysis of the atmo- spheric compensation and changes in the atmospheric heat transport is needed but is beyond the scope of our study.…”
Section: Discussionsupporting
confidence: 55%
“…FMR11 showed that enhanced OHT into midlatitudes stabilizes the large ice cap at equilibrium. The role of OHT in the equilibrated Warm state is more subtle (Rose and Ferreira 2013). Direct OHT convergence at the poles is small, except during transient cooling.…”
Section: Discussionmentioning
confidence: 99%
“…OHT at mid-to-high latitudes also scales with c res , collapsing as ice advances and resuming as ice retreats. There is little evidence that OHT scales with w Ek in the subpolar gyre, as assumed by Rose and Marshall (2009).…”
Section: Ocean Circulationmentioning
confidence: 98%
See 2 more Smart Citations